Comparative Analysis of Untargeted Metabolomics in Tolerant and Sensitive Genotypes of Common Bean (Phaseolus vulgaris L.) Seeds Exposed to Terminal Drought Stress - Mayavan Subramani; Carlos A. Urrea; Venu Kalavacharla (Metabolites, 2022)
Many environmental stresses can affect the accumulation of metabolites in plants, including drought. In the present study, we found a great deal of variability in the seed metabolic profiles of the tolerant (Matterhorn, SB-DT2 and SB-DT3) common bean genotypes in comparison to the sensitive genotypes (Sawtooth, Merlot and Stampede) using ultrahigh performance liquid chromatography−tandem mass spectrometry (UPLC-MS). The genotypes were grown in the field and subjected to drought stress after flowering (terminal drought stress). We aimed to investigate the accumulation of genotype-specific metabolites and related pathways under terminal drought stress by comparing tolerant and sensitive genotypes within a race. A total of 26 potential metabolites were identified across genotype comparisons. Significant metabolic pathways, including monobactam biosynthesis, flavone and flavonol biosynthesis, pentose phosphate pathway, C5-branched dibasic acid metabolism, cysteine and methionine metabolism, vitamin B6 metabolism and flavonoid biosynthesis, were derived from the enriched metabolites. Many of these metabolic pathways were specific and varied with genotype comparisons. SB-DT2 vs. stampede revealed more significant metabolites and metabolic pathways compared to Matterhorn vs. Sawtooth and SB-DT3 vs. Merlot under terminal drought stress. Our study provides useful information regarding the metabolite profiles of seeds and their related pathways in comparisons of tolerant and sensitive common bean genotypes under terminal drought conditions. Further research, including transcriptomic and proteomic analyses, may contribute to a better understanding of molecular mechanisms and nutritional differences among seeds of common bean genotypes grown under terminal drought conditions.